L’apport du concept de « dédoublement énonciatif » dans la description des séquences dialogiques - Biardzka, Elżbieta (Studia Romanica Posnaniensia, 2012)
This contribution follows the stream of “praxématique” researches which particularly focus on the dialogue contained in an enunciative split analyzable at the level of the performed enunciation, consisting in the insertion of a second-level enunciation into the main enunciation sequence. In this paper, heterogeneous modes of such enunciative insertions are examined in order to refine and / or rectify the theorization on enunciative split in the description of dialogical sequences. The dialogical mechanism of following text sequences are analyzed: “textual island” category (“îlot textuel”), the confirmation adverb “bien”, the cleft sentence (“clivage”) and the reported speech.